Ethics in Research with Human Subjects - A Brief Review - Khan, Md Uzire Azam; Amin, Md Ruhul; Begum, Firoza; Begum, Momotaz (Bangladesh Journal of Physiology and Pharmacology, 2010)
Ethics in research involving humans were first codified in 1946 as Nuremberg code. Subsequently other ethical declarations and guide lines were developed to protect the research participants as well as the researchers. The basic research bioethics includes three principles-respects for person, beneficence, and justice. To make a research with human subjects ethically sound the research protocol should have social and scientific values, fair subject selection, favorable risk benefit ratio, independent review, and informed consent of and respect for the participants. Above all the researcher should be honest and responsible enough to safeguard the rights and welfare of the research subjects. DOI: 10.3329/bjpp.v24i1.5734 Bangladesh J Physiol Pharmacol 2008; 24(1&2) : 24-26